The influence of resident seniority on supervised practice in the emergency department. Issue 4 (January 2017) - Chiu, I-Min; Syue, Yuan-Jhen; Kung, Chia-Te; Cheng, Fu-Jen; Lee, Chien-Hung; Lin, Yan-Ren; Li, Chao-Jui
Abstract : Abstract: To investigate the influence of resident seniority on supervised clinical practice in the emergency department (ED). This was a retrospective, 1-year cohort study conducted in 5 EDs within Taiwan largest healthcare system. All adult nontrauma visits presenting to the EDs during the day shift between July 1, 2011 and June 30, 2012 were included in the analysis. Visits were divided into supervised (ie, treated by resident under attending physician's supervision) and attending-alone. Supervised visits were further categorized by resident seniority (junior, intermediate, and senior). The decision-making time (door-to-order and door-to-disposition time), patient dispositions (eg, ED observation and hospital admission), and diagnostic tool use (laboratory examination or computed tomography [CT]) were selected as clinical performance indicators. The differences in clinical performance were determined between supervised visits (ie, resident-seniority groups) and attending-alone visits. Junior residents were found to have longer median door-to-order and door-to-disposition time than were the other residents for urgent and nonurgent patients. Furthermore, compared with attending-alone visits, supervised visits with junior residents had a greater odds of ED observation (adjusted odds ratio [aOR], 1.1; 95% CI, 1.07–1.20), while supervised visits with all 3 resident-seniority groups had significantly greater odds of laboratory examinations (junior: aOR, 1.1; 95% CI, 1.03–1.16; intermediate: aOR, 1.1; 95% CI, 1.04–1.15; and senior: aOR, 1.1; 95% CI, 1.05–1.15). As resident seniority increases, less time is needed for decision making in supervised visits. However, compared to attending-alone visits, supervised visits still resulted in greater use of laboratory examinations and delayed patient disposition.